2018
DOI: 10.1002/fut.21917
|View full text |Cite
|
Sign up to set email alerts
|

Short‐selling and credit default swap spreads—Where do informed traders trade?

Abstract: During the global financial crisis, short‐selling and credit default swaps (CDS) gained notoriety as indicators of financial collapse. This paper extends the literature by examining the relationship between short‐selling and CDS spreads. Results indicate that lagged short‐selling metrics forecast changes in CDS spreads; short‐selling is found to have a positive relationship with CDS spreads. These results are robust to various controls including the supply of stock for short‐selling, changes in CDS spreads, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Thus far, empirical studies that analyze short selling's impact on CDS spreads are rare. Prior works either examine short sales' impacts using proxy variables such as utilization -as the amount of stock that is lent for short selling as a percentage of the total amount available for stock lending -and short interest (Lecce et al 2018), or they consider establishing short sale bans to analyze short selling's general impact on the CDS market (such as those by Pereira da Silva 2016a; Pereira da Silva, Vieira, and Viegas Vieira 2016; Ni and Pan 2011; Pu and Zhang 2012).…”
Section: Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Thus far, empirical studies that analyze short selling's impact on CDS spreads are rare. Prior works either examine short sales' impacts using proxy variables such as utilization -as the amount of stock that is lent for short selling as a percentage of the total amount available for stock lending -and short interest (Lecce et al 2018), or they consider establishing short sale bans to analyze short selling's general impact on the CDS market (such as those by Pereira da Silva 2016a; Pereira da Silva, Vieira, and Viegas Vieira 2016; Ni and Pan 2011; Pu and Zhang 2012).…”
Section: Related Literaturementioning
confidence: 99%
“…Recently, Lecce et al (2018) approach the question of relative information content from the perspective of informed traders' instrument selection. They examine CDS contracts and short selling data between 2006 and 2008 to identify which trading venue first reveals signs of informed trading.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also examined the predictability of CDS spreads. For example, Lecce, Lepone, McKenzie, Wong, and Yang (2018) found that lagged short-selling metrics forecast changes in CDS spreads. However, we have little understanding about what drives the variations in sovereign CDS spreads.…”
mentioning
confidence: 99%